THE EFFECT OF EXCHANGE RATE AND INFLATION ON INDONESIAN EXPORTS IN 1989-2019 - Silalahi, Sonya Marintan; Iranto, Dicky; Sebayang, Karuniana Dianta (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2021)
This study aims to determine the effect of the exchange rate on Indonesian exports and the effect of inflation on Indonesian exports. The research model used in this study is the VECM (Vector Error Correction Model) with the Eviews 10 program tool. Using time series data in the time range used is 1989 to 2019 the type of data used is secondary data obtained from the site the official website of the relevant institutions such as the Central Statistics Agency, Bank Indonesia and other institutions. The results of the study that the exchange rate had a significant negative effect on exports in the short term from lag 1 to lag 4 had a coefficient value of -56,60425, - 55,73478, -46,13207 and -50,60992. Long term, the exchange rate had no significant effect on exports with a coefficient value of 25.8964. The estimation result of the VECM model in the short term inflation variable has a significant negative effect on lags 1 and 2 and the coefficient level is - 8.732157 and -6.818958 while in the longterm there is a significant positive effect with a coefficient value of 8.58546.